2017
DOI: 10.1208/s12248-017-0051-2
|View full text |Cite|
|
Sign up to set email alerts
|

Reliable Rate Measurements for Active and Passive Hepatic Uptake Using Plated Human Hepatocytes

Abstract: Transporter-mediated hepatic uptake is proven to be the rate-determining step in the systemic clearance of several drugs. Therefore, accurate measurement of active and passive uptake clearances in vitro is critical to facilitate pharmacokinetics and drug-drug interaction predictions. Here, we evaluated the plated human hepatocytes (PHH) and studied the effect of incubation temperature and inhibitor concentration on uptake measurements, in order to reliably estimate hepatic uptake components. Uptake rates measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(76 citation statements)
references
References 42 publications
3
72
1
Order By: Relevance
“…All active rates, CL HEP,pass , K M,HEP,uptake , and K M,HEP,efflux are estimated by fitting observed experimental data. In the presence of 1 mM inhibitor RSV, all active processes are fixed at zero based on a previous study (Bi et al, 2017). Although RSV is usually used as a transporter inhibitor, in-house data show that at 1 mM, P450-mediated metabolism is inhibited as well.…”
Section: Human and Monkey Hepatocyte Uptake Assay And A Mechanistic Imentioning
confidence: 99%
“…All active rates, CL HEP,pass , K M,HEP,uptake , and K M,HEP,efflux are estimated by fitting observed experimental data. In the presence of 1 mM inhibitor RSV, all active processes are fixed at zero based on a previous study (Bi et al, 2017). Although RSV is usually used as a transporter inhibitor, in-house data show that at 1 mM, P450-mediated metabolism is inhibited as well.…”
Section: Human and Monkey Hepatocyte Uptake Assay And A Mechanistic Imentioning
confidence: 99%
“…In comparison with the increased success of quantitative prediction of CYP-mediated DDIs, the confidence in the successful prediction of OATP-mediated DDIs using in vitro data is still low (Gertz et al, 2013;Prueksaritanont et al, 2014;Jones et al, 2015;Bi et al, 2017;Yoshida et al, 2017). Therefore, the objective of our study was to evaluate the IVIVE of OATP inhibition potential using cynomolgus monkey as a preclinical model and to gain confidence in mechanistic translational approach to predict clinical DDIs mediated by these transporters.…”
Section: Discussionmentioning
confidence: 99%
“…Methods adopted for uptake studies are similar to those previously reported by our group (Bi et al, 2017(Bi et al, , 2018aMathialagan et al, 2017). Stock solutions of all compounds were made in DMSO.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of incubation (2 minutes), the cellular uptake was terminated by washing the cells four times with ice-cold transport buffer, and then the cells were lysed with 0.2 ml of 1% NP-40 in water (radiolabeled compounds) or methanol containing internal standard (nonlabeled compounds). Transporter functionality was validated using in vitro probe substrates: 0.5 mM [ 3 H]-cGMP (OAT2) or 0.5 mM rosuvastatin (OATP1B1) as described previously (Bi et al, 2017;Mathialagan et al, 2018). Intracellular accumulation was determined either by mixing the cell lysate with scintillation fluid followed by liquid scintillation analysis (PerkinElmer Life Sciences) for radiolabeled compounds or by liquid chromatography-tandem mass spectrometry (LC-MS/MS) analysis for nonlabeled compounds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation